2011
DOI: 10.2528/pier11030408
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric and Asymmetric Double Langmuir Probes Characterization of Radio Frequency Inductivley Coupled Nitrogen Plasma

Abstract: Abstract-The symmetric and asymmetric double Langmuir probe systems with their necessary driving circuits are developed for characterization of low pressure inductively coupled nitrogen plasma, generated and sustained with 13.56 MHz RF source and an automatic impedance matching network. First of all, the plasma parameters such as ion saturation current, electron temperature and electron number density are determined with symmetric double probe system at different input RF powers, filling gas pressures and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…4, it is observed that kT e increases with increase of ac input voltage. [18]. This increasing trend in kT e under the influence of rising ac input voltage might be due to the increase in kinetic energy of the discharge plasma electrons.…”
Section: Discussionmentioning
confidence: 99%
“…4, it is observed that kT e increases with increase of ac input voltage. [18]. This increasing trend in kT e under the influence of rising ac input voltage might be due to the increase in kinetic energy of the discharge plasma electrons.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of plasma electron number density using Langmuir probes have proved that the increase of input RF power at a fixed filling gas pressure increases the plasma density in the column [18,19] and plasma frequency is a function of plasma density. Increasing the plasma frequency in the column increases the conductivity and consequently it causes considerable increment in the values of the gain, RCS and efficiency of a plasma antenna.…”
Section: The Effects Of the Plasma Frequencymentioning
confidence: 99%
“…The interest in surface plasmon polariton plasma metal is limited because it was believed that is impossible to satisfy boundary conditions at these interfaces. However, experiments show that propagation of surface wave is possible along metal plasma interfaces due to fact that metal and plasma walls are not in direct contact but are separated by each other by a sheet in which plasma behave as dielectric layer [18][19][20]. The surface wave produced between plasma metal interface are characterized by terms of plasma parameters such as plasma electron density, collisional frequency for their exceptionally tuneability whether external magnetic field present or absent in plasma [21,22].…”
Section: Introductionmentioning
confidence: 99%